Family Communication in Qur'an - Nurhalima Tambunan (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Communication is the essential part of family life; family relationships will be harmonious if established good communication in family members. It can also be seen and understood from the meaning of communication derived from the Latin word “communicatio.” It has the same meaning. From some communication that happened in family,the author only discuss communication between child and parent in the family according to Al-Quran Surah Al Isra 23-24 and Al-Luqman 14-15. Family communication is an organization that uses words, gestures, the intonation of sounds, actions to create image expectations, expressions of feelings and mutual understanding. Words, posture, the intonation of sounds and actions, contain the intent to teach, influence and give understanding. The main purpose of this communication is initiating and maintaining interaction between one member with other members to create effective communication. The communication between the child and the parent in verse is to instruct, to require and oblige the duties of both parents by not showing contradiction or rebellion to both. The devotion to parents is not special when both parents are Muslim. Even if both unbelievers, worship and do good to both remain obligatory.